Anti-inflammatory effect of glucose-mannose binding lectins isolated from Brazilian beans - A. M. S. Assreuy; M. D. Shibuya; G. J. Martins; M. L. P. De Souza; B. S. Cavada; R. A. Moreira; J. T. A. Oliveira; R. A. Ribeiro; C. A. Flores (Hindawi Limited, 1997)
Selectins are essential for leukocyte recruitment in inflammation. Because of a lectin domain present in the selectin structure, we investigated the anti-inflammtory activity of six mannose-glucose binding lectins from brazilian beans: Dioclea guianensis-DguiL; D. grandiflora-DgL; Cratylia floribunda-CfL; D. violacea-D.vL; D. virgata-DvirL and Canavalia brasiliensis-ConBr. The lectins were injected intravenously (i.v.) into rats (0.1 and 1.0 mg/kg; 30 min before irritants) and its activities compared to E. coli endotoxin (LPS,30 μg/kg i.v.). Three lectins (DvL, CfL and DguiL), although less intense than LPS, inhibited the neutrophil migration induced by carrageenan (Cg, 300 μg) in a dose-dependent manner (0.1 and 1.0 mg/kg). DvL activity was reversed by 0.1 M α-D-methyl-mannoside (α-CH3), but not by 0.1 M α-D-galactose. The fMLP (44 ng)-induced neutrophil migration was also reduced by these lectins. Endotoxin contamination of lectin samples could be excluded since α-CH3 treatment reversed the DvL effect, but did not modify LPS inhibitory activity. Carrageenan (300 μg)-induced paw oedema was also reduced by LPS or lectin treatments. Conversely, none of the tested lectins inhibited dextran (Dex, 300 μg)-induced paw oedema, a classical leukocyte independent model, or zymosan (Zy, 1.0 mg)-induced peritonitis and paw oedema. LPS showed no effect upon Dex-induced paw oedema and barely reduced (25%) the oedematogenic effects of zymosan. As proposed for LPS, the lectin inhibitory activity was better observed on neutrophil-mediated inflammatory reactions. We speculate that the plant lectin antiinflammatory activity is probably due to a competitive blockage of a common leukocyte and/or endothelial selectin carbohydrate ligand.